O Centro Educacional São José Operário em São Luís do Maranhão (1988-2015): confessionalidade e laicidade - Rodrigues, Maria José Lobato (Universidade Federal de São Carlos, 2020)
This study analyzes the trajectory of Centro educacional São José operário (CESJO), founded by the Congregation Poor Servants of Divine Providence, in Maranhão capital, in 1988, to attend the sons of poor families from the periphery of São Luís. As a philanthropic confessional school, the CESJO express, by one side, elements that fundament the educative and caritive intentions of the catholic church, and, by other, when being financed with public resources, the secularity of the state. In this sense, the analysis is justified by permit comprehend the catholic interaction present in the school inside of the context of secularity of the state in the education. The study self insert in the field of history of education and, more specifically, in the line of the educational institutions where we search for theoretical. Methodolocally, we stablished as temporal mark the period of time between 1988 and 2015 (27 years) by the possibility to reconstruct the tragetory of the institution and the transformations in which it passes nowadays. The study self insert in the field of history of education and, more specifically, in the line of the educational institutions, Aiming documental intersection using different sources, among them, the writings, iconographicals and orals, being that the interviews were of absolute importance especially by the fact of many pratices and experiences lived by different individuals in the school being only registred in their memories.The Congregation when creating the school found in the sucularity of the State the guarantees to offer for the society assistencial support and confessional school education that stablished their bases in the work as educative principle. CESJO’s confessional identity was marked by a set of rites and practices (disciplining, prayer, religious teaching classes, sacred symbols, religious festivities, congregational charism, spiritual formation), which, in turn, built own school culture that influenced the identity and worldview of their subjects. CESJO over three decades has changed its relationship with the State: between 1988-2003 it was configured as a philanthropic confessional school that received public resources; in 2004 it was inserted in the public education network; in 2015 the school building was rented to SEDUC-MA. The relationship he established with the public authorities since 2004 and the socio-cultural influences interfered with his confessional character and christian identity, making him characterized as a public school with elements of catholic confessionality. CESJO’s trajectory shows that the State-religion relationship produced a secularity in education marked by the influence and manifestation of religious elements in public spaces, what sustain the validity of christian educaction inside the education system.
The São José Operário educational center in São Luís do Maranhão (1988-2015): confessionality and secularity
Keywords: Educação escolar católica; Centro Educacional São José Operário (CESJO); Confessionalidade e laicidade; Catholic school education; Confessionality and secularity; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO